Biophysical mechanisms underlying the effects of static magnetic fields on biological systems. (January 2023) - Zhang, Bin; Yuan, Xichen; Lv, Huanhuan; Che, Jingmin; Wang, Shenghang; Shang, Peng
Abstract: With the widespread use of static magnetic fields (SMFs) in medicine, it is imperative to explore the biological effects of SMFs and the mechanisms underlying their effects on biological systems. The presence of magnetic materials within cells and organisms could affect various biological metabolism and processes, including stress responses, proliferation, and structural alignment. SMFs were generally found to be safe at the organ and organism levels. However. human subjects exposed to strong SMFs have reported side effects. In this review, we combined the magnetic properties of biological samples to illustrate the mechanism of action of SMFs on biological systems from a biophysical point of view. We suggest that the mechanisms of action of SMFs on biological systems mainly include the induction of electric fields and currents, generation of magnetic effects, and influence of electron spins. An electrolyte flowing in a static magnetic field generates an induced current and an electric field. Magnetomechanical effects include orientation effects upon subjecting biological samples to SMFs and movement of biological samples in strong field gradients. SMFs are thought to affect biochemical reaction rates and yields by influencing electron spin. This paper helps people how can harness the favorable biological effects of SMFs.